Sarana Pengetahuan Ilmiah (Tinjauan Filosofis) - Firmansyah; Mukti Ali (LP3M Universitas Al-Qur'an Ittifaqiah Indralaya, 2021)
In order to always be able to exist and develop their lives, humans will continue to develop knowledge through a learning process that starts from a philosophical thought using a scientific thinking pattern. In the scientific context, not all philosophical thought processes can be said to be scientific knowledge. In addition, scientific knowledge also requires a means to actualize it. This research intends to find out: 1) what is meant by scientific knowledge? and 2) what are the means of scientific knowledge? This research is library research. Research data collection was carried out using documentation techniques. The data analysis used inductive analysis. Based on the data analysis that has been done, it can be concluded that scientific thinking is thinking with the steps of the scientific method such as problem formulation, hypothesis submission, literature review, testing hypotheses and drawing conclusions. All steps of thinking with the scientific method must be supported by good tools/means, so it is hoped that the results of the scientific thinking that we do get good results too. To be able to carry out scientific thinking activities properly, facilities in the form of language, logic, mathematics and statistics are needed.